2013
DOI: 10.1152/ajpendo.00208.2013
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucose tolerance in rats fed low-carbohydrate, high-fat diets

Abstract: Tschöp MH, Seeley RJ, Bidlingmaier M. Impaired glucose tolerance in rats fed low-carbohydrate, high-fat diets. Am J Physiol Endocrinol Metab 305: E1059 -E1070, 2013. First published August 22, 2013; doi:10.1152/ajpendo.00208.2013.-Moderate low-carbohydrate/high-fat (LC-HF) diets are widely used to induce weight loss in overweight subjects, whereas extreme ketogenic LC-HF diets are used to treat neurological disorders like pediatric epilepsy. Usage of LC-HF diets for improvement of glucose metabolism is highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 56 publications
8
61
0
2
Order By: Relevance
“…This was also observed in a recent study by Bielohuby et al after 4 wk of KD in mice (4). We now show that insulin concentrations were increased to maintain normoglycemia after 1 wk of KD, but continuation of the KD resulted in insufficient insulin secretion to maintain glucose tolerance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This was also observed in a recent study by Bielohuby et al after 4 wk of KD in mice (4). We now show that insulin concentrations were increased to maintain normoglycemia after 1 wk of KD, but continuation of the KD resulted in insufficient insulin secretion to maintain glucose tolerance.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, several short-term studies in rodents have shown that KD leads to hepatic steatosis, insulin resistance, and glucose intolerance (4,16,20).…”
mentioning
confidence: 99%
“…Studies which directly examined the impact of high-fat, high-protein, low-carbohydrate diets on insulin sensitivity have reported conflicting findings, with some showing that such diets lead to glucose intolerance and insulin resistance (2)(3)(4)19), and others reporting it prevents insulin resistance (22), or causes no change in insulin resistance (5,8). While we found a steady progression of insulin-dependent Akt phosphorylation (taken as a measure of insulin effect) in hearts of animals fed CONT diet, there was an unusual response to insulin in the HFLCD-fed heart, with an initially high baseline amount of p-Akt at very low insulin levels and a blunted response as the dose was increased.…”
Section: Discussionmentioning
confidence: 99%
“…In the 13 C NMR spectrum on the right, K represents isotopomer peaks derived from ketone (3-HB); C represents those derived from carbohydrate (glucose, lactate, and pyruvate). Note that ␤-oxidation of [1][2][3][4][5][6][7][8][9][10][11][12][13] C]palmitate results in seven unlabeled acetyl-CoA fragments and one [1-ketone buffer, high insulin led to decreased FFA oxidation and upregulated ketone oxidation (P Ͻ 0.05 for high insulin compared with low insulin with the same ketone level, perfusion condition, and diet); this effect was not seen with low ketone buffer. At the low level insulin buffer, high ketone upregulated FFA oxidation and decreased ketone oxidation (P Ͻ 0.05 in the HFLCD group for high ketone compared with low ketone with the same insulin level, perfusion condition).…”
Section: Impact Of Perfusion Buffer Composition (Insulin and Ketone Lmentioning
confidence: 99%
“…Most of the food items available are categorically rich in fat and simple carbohydrates. Food influences hormones such as insulin [1,2] and leptin [3,4]. Insulin and leptin, both anorexic hormones, are known to suppress appetite [5].…”
Section: Introductionmentioning
confidence: 99%